Simultaneously High Thermal Stability and Low Power Based on Ti-Doped Ge2Sb2Te5 Thin Films. (1st January 2017) - Hu, Yifeng; Zhang, Rui; Lai, Tianshu; Zhu, Xiaoqin; Zou, Hua; Song, Zhitang
Abstract : Compared with Ge2 Sb2 Te5, Ti-doped Ge2 Sb2 Te5 has better amorphous thermal stability (activation energy of 4.65 eV) and data retention (165°C for 10-year). The crystallization is restrained by the added Ti atoms with smaller grains. A faster SET/RESET switching speed (12 ns) and a lower RESET voltage (2.67 V) are obtained. The results indicate that Ti-doped Ge2 Sb2 Te5 material has the excellent potential for high-density application in phase change memory.